INFLUENCE OF BIOLOGICAL PREPARATIONS ON THE NUMBER MICROMYCETES OF RHIZOSPHERIC SOIL THE SPRING BARLEY PLANTS - Mosiychuk І.; Beznosko, I.; Gorgan, T.; Havrylyuk, L.; Mineralova, V. (Scientific Progress & Innovations, 2022)
Biological preparations have the ability to regulate the life processes of plants and soil microflora, to mobilize potential opportunities formed in the genome thanks to nature and selection. Therefore, the purpose of our study was to investigate the influence of biological preparations Oracle multicomplex, Pennant 2 and the mixture Oracle multicomplex + Pennant 2 to the number of rhizosphere soil micromycetes of different varieties of Sebastian and Helios spring barley. The number of micromycetes in the rhizosphere soil of spring barley was the lowest during the effect of the mixture of Oracle multicomplex + Vimpel 2 preparations, which was from 5.0 to 7.0 million CFU g/soil. The number of micromycetes in the rhizosphere soil of spring barley also decreased significantly under the influence of the Oracle multicomplex preparations, which averaged 5.5 million CFU/g of soil and Vimpel 2. Their number under sowing of both varieties reached 6.0–8.0 million CFU/g soil. At the same time, the number of micromycetes was 1.5–2 times higher on the control version. In the budding and flowering phase, 9 genera of micromycetes parasitized the control variant: Fusarium spp., Chaetomium spp., Cladosporim spp., Alternaria spp., Aspergillus spp., Trichoderma spp., Acremonium spp., Bipolaris spp. and Penicillium spp. Their frequency of occurrence was up to 20 % on the Sebastian variety and up to 15 % on the Helios variety. In the ripening phase, the number of rhizosphere soil micromycetes increases and the frequency of occurrence of these species increases significantly to 70 %. During the action of Oracle multicomplex, Vympel 2 and their mixture, a smaller number of species of rhizosphere soil micromycetes was observed with a significantly lower frequency of occurrence, which reached 4–35 %. The spring barley variety Helios is able to have a greater effect on the number of micromycetes in the rhizosphere soil compared to the Sebastian variety under the influence of biological preparations. It depends on the properties of the variety's plants, which are characterized by a certain set of physiological and biochemical characteristics that affect the number and quantitative composition of soil micromycetes. The use of these drugs in crops will help reduce the accumulation of infectious structures in agrocenoses and provide an opportunity to obtain ecologically clean, high-quality organic products.